Analisis Perbedaan Pendapatan Usahatani Padi Sawah Sistem Tanam Jajar Legowo 2 : 1 Dengan 4 : 1 di Kecamatan Kualuh Selatan Kabupaten Labuhanbatu Utara - Safriadi, Safriadi; Siregar, Tumpal H. S.; Khardinata, E. Harso (Universitas Medan Area, 2020)
This study aims to determine the differences in income and determine the feasibility of a 2: 1 to 4: 1 jowo legowo planting system in rice farming. The form of this research is a quantitative study with survey and observation methods in the field. The population in this study was the community of paddy rice farmers in 3 villages namely Siamporik village, Gunung Melayu village and Siduadua village in Kualuh Selatan District of North Labuhanbatu Regency and purposive sampling technique. The results showed that the legowo row 2: 1 with 4: 1 planting systems were significantly different in terms of static income, the average income of Jarwo 2: 1 farmers was 14,315,331 and Jarwo 4: 1 was 13,863,238 with R / C Jarwo 2: 1 ratio of 1,247 and Jarwo 4: 1 of 1,204, for Jarwo 2: 1 BEP analysis 4,970 and Jarwo 4: 1 BEP analysis of 5,065.